Synthesis and applications of TEOS PDMS hybrid material by the sol-gel process - Kim, GD; Lee, DA; Moon, JW; Kim, JD; Park, JA (JOHN WILEY & SONS LTD, 1999)
An organically modified silicate, ormosil, was synthesized with an inorganic precursor, (tetraethoxysilane, TEOS) and an organic precursor [poly(dimethylsiloane), PDMS] through sol-gel chemistry. The bonding characteristics of the composite were investigated via glass transition temperatures (T-g) and a hybridization model of TEOS and PDMS was illustrated schematically. The variation of T-g with the ratios of HCI/TEOS and TEOS/PDMS was observed. Ormosil sols for coating were obtained with TEOS/PDMS ratios from 60:40 to 90:10 and the best ormosil sol as the host of a dye laser was obtained from a ratio of 90:10. As the HCI/TEOS ratio was increased, higher T-g values were obtained but holes formed in the coated surface and laser output diminished. Dimerization of organic molecules was detected in the enlarged pore size of the host due to an increase in the ratio. The effects of HCl and PDMS on bonding characteristics were measured by dynamic mechanical thermal analyser (DMTA). UV/VIS spectrophotometry, spectrofluorimetry and scanning electron micrography (SEM) were used to obtain the properties relating to this study of inorganic-organic composites. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: INORGANIC GLASSES; ACID CONTENT; CERAMERS; CERAMICS